Ethanol Inhalation for Respiratory Infections due to Enveloped Viruses - Pietro Salvatori; Ali Amoushahi; Aldo Venuti; Francesca Paolini (Infectious Diseases and Therapy)
Abstract Ethanol has demonstrated high efficacy in inactivating enveloped viruses in vitro and in vivo (in animal and human studies). The inhalation route has been a significant method of drug administration for respiratory disorders since ancient times. Infections with enveloped viruses cause many respiratory diseases. This concise review explores the general structural characteristics of enveloped viruses and examines the potential role of inhaled ethanol as a low-cost therapy for respiratory diseases. Current literature data suggest that ethanol inhalation could be beneficial in treating respiratory infections caused by enveloped viruses. However, there is a clear gap in well-designed clinical trials assessing the safety and efficacy of ethanol inhalation in treating respiratory infections from enveloped viruses. This low-cost therapy could become an important therapeutic option, especially for large numbers of patients simultaneously infected, as was the case during the coronavirus disease 2019 (COVID-19) pandemic. In addition, inhaled ethanol could be a successful approach for vulnerable patients such as patients with cancer because it is likely to have no or minimal effects on already established life-saving treatments. Further investigation by national and international institutions is urgently needed to validate these findings and refine treatment protocols.